Out of the Loop: Why Research Rarely Reaches Policy Makers and the Public and What Can be Done - Shanley, Patricia; López, Citlalli (Biotropica, 2009)
Most of the world's population that derives their livelihoods or part of their livelihoods from forests are out of the information loop. Exclusion of public users of natural resources from access to scientific research results is not an oversight; it is a systemic problem that has costly ramifications for conservation and development. Results of a survey of 268 researchers from 29 countries indicate that institutional incentives support the linear, top-down communication of results through peer-reviewed journal articles, which often guarantees positive performance measurement. While the largest percentage of respondents (34%) ranked scientists as the most important audience for their work, only 15 percent of respondents considered peer-reviewed journals effective in promoting conservation and/or development. Respondents perceived that local initiatives (27%) and training (16%) were likely to lead to success in conservation and development; but few scientists invest in these activities. Engagement with the media (5%), production of training and educational materials (4%) and popular publications (5%) as outlets for scientific findings was perceived as inconsequential (<14%) in measuring scientific performance. Less than 3 percent of respondents ranked corporate actors as an important audience for their work. To ensure science is shared with those who need it, a shift in incentive structures is needed that rewards actual impact rather than only 'high-impact' journals. Widely used approaches and theoretical underpinnings from the social sciences, which underlie popular education and communication for social change, could enhance communication by linking knowledge and action in conservation biology.